Effect of nitrogen injection time on structural and mechanical properties of AlN particles in aluminum matrix composite by in-situ gas bubbling method - Nguyen Quoc, Tuan; Duong Van, Thiet; Nguyen Tien, Tung; Pham Van, Dong (Vietnam Journal of Science and Technology, 2025)
In this paper, we report on the effect of nitrogen injection time on formation of AlN crystal particles in aluminum matrix by in-situ gas-bubbling method. The magnesium content with 15 wt.% was added into Al matrix as a catalyst. The results show that AlN polycrystalline particles were formed with hexagonal structures, featuring lattice constants c = 4.969 Å and a = 3.107 Å. The crystallite size was decreased as increased nitrogen injection time,while the AlN particles density and micro-hardness were increased. The SEM images indicated that the AlN particles size varies from a few hundred nm to several µm. The micro-hardness testing was conducted using ISOSCAN HV2 AC instrument, and the highest value of sample obtained was 120 HV at nitrogen injection of 4 hours. The fabrication of AlN/Al composite using the in-situ gas-bubbling method is still a potential application for manufacturing industrial large scale.